2010
DOI: 10.1111/j.1365-2826.2010.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Nonpeptide (Ant)agonists to Rescue Vasopressin V2 Receptor Mutants for the Treatment of X‐linked Nephrogenic Diabetes Insipidus

Abstract: Maintaining the water homeostasis of the body is crucial for its proper functioning. Accordingly, water and electrolytes are balanced by a carefully orchestrated interplay between volume-and osmoregulation that is regulated by multiple hormones. A key hormone in process is the antidiuretic hormone arginine-vasopressin (AVP), which is released from the pituitary in states of hypernatreamia or hypovolaemia (1, 2).The main target organ of AVP in the process of osmoregulation is the kidney, which is composed of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 36 publications
0
32
0
2
Order By: Relevance
“…Other potential treatments for NDI include possible rescue of trapped V 2 receptors stuck in the endoplasmic reticulum, as seen with class II mutations [78,135]. Rescue of these receptors via chemical compounds known as nonpeptide chaperones looks to be promising [78]. These nonpeptide chaperones stabilize the V 2 receptor trapped in the endoplasmic reticulum of the collecting duct cells.…”
Section: Ndimentioning
confidence: 99%
See 2 more Smart Citations
“…Other potential treatments for NDI include possible rescue of trapped V 2 receptors stuck in the endoplasmic reticulum, as seen with class II mutations [78,135]. Rescue of these receptors via chemical compounds known as nonpeptide chaperones looks to be promising [78]. These nonpeptide chaperones stabilize the V 2 receptor trapped in the endoplasmic reticulum of the collecting duct cells.…”
Section: Ndimentioning
confidence: 99%
“…DDAVP usually has no effect on patients with NDI but may be effective in patients with partial resistance to ADH; therefore, it is worthwhile to try a high dose of DDAVP [134]. Other potential treatments for NDI include possible rescue of trapped V 2 receptors stuck in the endoplasmic reticulum, as seen with class II mutations [78,135]. Rescue of these receptors via chemical compounds known as nonpeptide chaperones looks to be promising [78].…”
Section: Ndimentioning
confidence: 99%
See 1 more Smart Citation
“…Дильмана, основным звеном меха-низмов как развития, так и последующего старения орга-низма является гипоталамус. Главная причина старения -это возрастное снижение чувствительности гипотала-муса к регуляторным сигналам, поступающим от нервной системы и желез внутренней секреции [13]. На протяже-нии 60-80-х годов XX века с помощью эксперименталь-ных исследований и клинических наблюдений было уста-новлено, что именно этот процесс приводит к возрастным изменениям функций репродуктивной и гипоталамо-ги-пофизарно-надпочечниковой систем, обеспечивающим необходимый уровень вырабатываемых корой надпочеч-ников глюкокортикоидов -«гормонов стресса», суточ-ным колебаниям их концентрации и повышению секре-ции при стрессе, и в конечном итоге к развитию состоя-ния так называемого «гиперадаптоза».…”
Section: теория гликозилирования белковunclassified
“…This can be done with the help of chemicals known as nonpeptide chaperones. 74,75 Recent studies have shown that gene therapy can be the better option for treatment of NDI but it is highly speculative. 24 Recent investigations have revealed that statins also increase the expression of AQP2 in apical membrane.…”
Section: Nephrogenic Diabetes Insipidusmentioning
confidence: 99%